Pengaruh Promosi, Tingkat Harga dan Lokasi terhadap Keputusan Pembelian Rumah Berwawasan Syariah di Puri Nirana Cigelam Purwakarta - Putri Zafira Ruhliandini (Masoem University, 2023)
The purpose of this study was to determine how much influence the promotion, price level, and location on the purchase decision of sharia-minded homes in Puri Nirana Cigelam Purwakarta, either partially simultaneusly. This research is objective, using quantitative methods and included in explanatory research. As both, because this study connects three variables, namely the implementation of promotions, price levels, and locations. Based on the results of the study, promotion variables, price levels, and location simultaneously have positive and significant influence on purchasing decisions of 93.4%. From the results of calculations using SPSS 16.0 for Windows, it shows that Fcount> Ftable ie, 562,106> 2.67 then Ha is accepted and H0 is rejected, which means that simultaneously there is a significant influence between promotion (X1), price level (X2), and location (X3) on purchasing decisions (Y).